Crossbow impact effect on clothing and potential associated injuries - Critchley, Richard; Hennessy, Niall P.; Read, James; Hazael, Rachael (Wiley, 2025)
There has been an increase in crossbow use for hunting practices, sport target shooting, and criminal activity. In the UK, there is minimal legislation surrounding the crossbow. UK law states individuals must be over 18 to buy or possess a crossbow. To date, little experimental research has been conducted, with most of the research focusing on injuries resulting from crossbow incidents. The aim of this study was to ascertain what effect crossbow bolts would have against ordinary clothing worn by the public and how or if different combinations of clothing would fare differently against the bolts and if that could be of use to the forensic examiner. An 80 lb. Armex tomcat II crossbow was used with three types of clothing used in four combinations, along with a non‐clothed gelatine block. The results showed that all 10 bolts penetrated the non‐clothed gelatine block, T‐shirt, and polo shirt series, while nine bolts penetrated the hoodie/T‐shirt combination and only three penetrated the hoodie/polo shirt combination. Significant differences were highlighted between the mean penetration depths of the non‐clothed gelatine block and each clothing series, with the highest observed value being the thickest layer combination. Inspections of bolts and wound tracts revealed the presence of clothing fibers. The conclusions of this study demonstrated that this information can be utilized by forensic investigators and medical professionals as a source of trace evidence. Further research into crossbow effects on clothing would prove beneficial to increase the understanding of how the crossbow reacts with the environment.
Keywords: Legal & Forensic Medicine; 3199 Other biological sciences; 3499 Other chemical sciences; 4402 Criminology; ballistic injury; crossbow impact; fabric damage; fiber transfer; gelatine; non-penetrating injury; penetrating injury